Intracerebral Transplantation of Mesenchymal Stromal Cell Compounded with Recombinant Peptide Scaffold against Chronic Intracerebral Hemorrhage Model. (31st July 2022) - Takamiya, Soichiro; Kawabori, Masahito; Kitahashi, Tsukasa; Nakamura, Kentaro; Mizuno, Yuki; Yasui, Hironobu; Kuge, Yuji; Tanimori, Aki; Takamatsu, Yasuyuki; Yuyama, Kohei; Shichinohe, Hideo; Fujimura, Miki
Abstract : Background . Due to the lack of effective therapies, stem cell transplantation is an anticipated treatment for chronic intracerebral hemorrhage (ICH), and higher cell survival and engraftment are considered to be the key for recovery. Mesenchymal stromal cells (MSCs) compounded with recombinant human collagen type I scaffolds (CellSaics) have a higher potential for cell survival and engraftment compared with solo-MSCs, and we investigated the validity of intracerebral transplantation of CellSaic in a chronic ICH model. Methods . Rat CellSaics (rCellSaics) were produced by rat bone marrow-derived MSC (rBMSCs). The secretion potential of neurotrophic factors and the cell proliferation rate were compared under oxygen-glucose deprivation (OGD) conditions. rCellSaics, rBMSCs, or saline were transplanted into the hollow cavity of a rat chronic ICH model. Functional and histological analyses were evaluated, and single-photon emission computed tomography for benzodiazepine receptors was performed to monitor sequential changes in neuronal integrity. Furthermore, human CellSaics (hCellSaics) were transplanted into a chronic ICH model in immunodeficient rats. Antibodies neutralizing brain-derived neurotrophic factor (BDNF) were used to elucidate its mode of action. Results . rCellSaics demonstrated a higher secretion potential of trophic factors and showed better cell proliferation in the OGD condition. Animals receiving rCellSaics displayed better neurological recovery, higher intracerebral BDNF, and better cell engraftment; they also showed a tendency for less brain atrophy and higher benzodiazepine receptor preservation. hCellSaics also promoted significant functional recovery, which was reversed by BDNF neutralization. Conclusion . Intracerebral transplantation of CellSaics enabled neurological recovery in a chronic ICH model and may be a good option for clinical application.